2001
DOI: 10.1002/ijc.10175
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy with hypericin induces vascular damage and apoptosis in the RIF‐1 mouse tumor model

Abstract: Hypericin, a polycyclic quinone obtained from plants of the genus Hypericum, has been proven to be a potent photosensitizer. The mechanism of tumor eradication and mode of cell death induced by in vivo photodynamic therapy (PDT) with hypericin were investigated in the present study using 2 therapeutic protocols. RIF-1 tumors were exposed to laser light at either 0.5 hr or 6 hr after hypericin administration (5 mg/kg, i.v.). A significant reduction in tumor perfusion, as determined by the retention of fluoresce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
64
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 26 publications
6
64
1
Order By: Relevance
“…We have recently been focusing on hypericin, a natural compound isolated from Hypericum plants (Lavie et al, 1995a), as a potent photosensitiser with a high antitumoral PDT efficacy (Chen and de Witte, 2000;Chen et al, 2001Chen et al, , 2002. In the course of our study, we found that the compound accumulated to a large extent in tumour tissues.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…We have recently been focusing on hypericin, a natural compound isolated from Hypericum plants (Lavie et al, 1995a), as a potent photosensitiser with a high antitumoral PDT efficacy (Chen and de Witte, 2000;Chen et al, 2001Chen et al, , 2002. In the course of our study, we found that the compound accumulated to a large extent in tumour tissues.…”
mentioning
confidence: 77%
“…The RIF-1 and R1 tumour-bearing animals were used to quantify the tumour perfusion by means of spectrofluorometric determination of tumour FITC-dextran uptake (fluorescein isothiocyanate dextran, M r 2 Â 10 6 , obtained from Sigma, St Louis, MO, USA), as described (Chen et al, 2002).…”
Section: Tumour Blood Perfusionmentioning
confidence: 99%
“…There is an extensive body of literature that examines the pathways of apoptosis that are induced after PDT in both normal and tumour cells in tissue culture, such as signalling pathways 30,31 , mitochondrial events 4 and mediators of apoptosis 32 . The occurrence of apoptosis after PDT in tumours in vivo has also been shown [33][34][35] , but there have been no studies looking at in vivo clearance mechanisms of apoptotic cells in tumours after PDT.…”
Section: Effects Of Pdt On Tumour Cellsmentioning
confidence: 99%
“…There is an extensive body of literature that examines the pathways of apoptosis that are induced after PDT in both normal and tumour cells in tissue culture, such as signalling pathways 30,31 , mitochondrial events 4 and mediators of apoptosis 32 . The occurrence of apoptosis after PDT in tumours in vivo has also been shown [33][34][35] , but there have been no studies looking at in vivo clearance mechanisms of apoptotic cells in tumours after PDT.Many studies have examined the relationship between the mode of tumour cell death (by methods other than PDT) and the efficiency of induction of the immune response, both in 36,37 . Although some reports show that apoptotic tumour cells are more effective than necrotic tumour cells at inducing an immune response 38,39 , there are other reports that show that modes of cancer therapy that predominantly induce necrosis are actually better at activating the immune system than methods that predominantly induce apoptosis 40,41 .…”
mentioning
confidence: 99%
“…72 Antibodies against LC3 (3868) and SERCA2 (4388) were from Cell Signaling Technology. Anti-Cyt C antibody (556433) Figure 4D and E. Secondary ROS modulate organelle-specific autophagy.…”
Section: Chemicalsmentioning
confidence: 99%